Pendampingan Pembuatan Website Dalam Rangka Meujudkan Keterbukaan Informasi Publik Desa Jambu, Kabupaten Tebo - Zulkifli; Pratiwi, Widya; Tarjo; Hamirul; Burhanuddin; Darmawanto; Hasdani (HIMPUNAN DOSEN GEMILANG INDONESIA, 2022)
Currently the world of information technology is developing rapidly with the use of the internet which is increasingly global. The internet here as a transmitter of information, its existence has now become a human need. The benefits of the internet are quite large, especially in the world of business, entertainment and education. Jambu Village is one of the villages in Tebo Ulu District. Nangsri Village is a government agency engaged in community services experiencing problems in the system of introducing organizational structures, activities, locations, which are currently only known by the surrounding community. With the development of this Information Technology, it encourages the author to design a Website Profile of Jambu Village with the creation of this website, it is hoped that it will run well and can be felt the benefits, it will make it easier to introduce the potentials, activities, that exist in Jambu Village and the community can find out the developments that have occurred. occurred in Jambu Village, especially the community around Jambu Village and more broadly it can be known by all people in the world. The purpose of this service is to build a Website Profile of Jambu Village, Tebo Ulu District, Tebo Regency. The benefit of this service is that in addition to what is listed above, it is hoped that the existence of a Website in Jambu Village can optimize in conveying information about the potential organizational structure in Jambu Village. The method of this research is data collection, data analysis, design, programming, testing and implementation. With the construction of the Jambu Village profile website, it is easier to market products in Jambu Village so that it can be known by the wider community, especially the Jambu Village community, they don't have to come directly to Jambu Village, just look through the website to find out the information in the Jambu Village.